Risk Management in Modular Construction and Offsite Manufacturing: Challenges, Opportunities, Trends and Technological Solutions - Sandra T. Matarneh; Zaid Ahmad Malak (Journal of Construction in Developing Countries, 2026)
This study systematically reviewed 87 peer-reviewed publications from 2002 to 2024 to explore the challenges and opportunities in modular construction and offsite manufacturing, with a specific focus on risk management. Using six-step thematic analysis framework by Braun and Clarke, this review identified three critical barriers to the adoption of advanced technologies: (1) logistical complexities in transportation and site coordination, (2) stakeholder fragmentation leading to communication breakdowns and (3) regulatory inconsistencies that hinder scalability. To address these challenges, the study highlighted three transformative digital solutions: (1) digital twins for real-time monitoring and scenario planning, (2) the Internet of Things for enhanced coordination and data transparency and (3) artificial intelligence for predictive analytics and decision support. The findings revealed that offsite manufacturing and modular construction offer significant benefits in terms of sustainability, cost savings and time efficiency. However, achieving full-scale adoption requires harmonised regulatory frameworks, targeted training initiatives to address skill gaps and policies that support digital technology integration. The study concludes with a call for coordinated action among policymakers, industry stakeholders and educators to facilitate technology-driven transformation in modular construction and maximise its contribution to sustainable and resilient infrastructure development.